Best price for my garlic - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Best price for my garlic , Down to Earth (Centre for Science and Environment, India, 2001) Padma Bai, a farmer from Madhya Pradesh, sold her garlic the day before she first came across a computer.